Purposeful game como freio da desinformação contemporânea : o caso do super gotinha VS sinformação - Bourscheid, Ana Paula (2023)
Purposeful games are designed to collect, from human interaction with the game narrative, data that could not be produced by computational machines in order to identify ways that can solve social and scientific problems (STAPLES, 2011; LAFOURCADE et al., 2015). It is based on this definition that the research theme of this thesis originates, the purposeful game as an alternative that uses native resources of games to disseminate the concept of disinformation in contemporary times. The general objective of the study is to investigate the informative and pedagogical potential of the purposeful game with a view to disseminating the concept of disinformation in contemporary times, from the production of a purposeful game for digital platforms. With this purpose, an applied research was developed (SANTOS, 2018; 2020) organized based on the methodological procedures of Action Research (THIOLLENT, 2011) and which resulted in the creation and publication of the purposeful game Super Gotinha VS Desinformação, available in https://supergotinha.github.io/jogo/. The product, developed with a low budget by a multidisciplinary team, was tested by young and adult students, a public identified as the age group that most plays games in the country, according to data from PGB (2022). The tests applied were carried out with students from the Youth and Adult Education Center (Ceja) of Chapecó - SC and the Individual Microentrepreneur Course (MEI) offered at the Federal Institute of Education, Science and Technology of Amapá - Ifap, Campus Santana-AP. Among the results of the research, it is observed that the purposeful game developed consists of an alternative to curb misinformation, since, to the extent that it provides the player with entertainment, it also teaches, informs, instructs and provokes reflection and public debate on misinformation involving human vaccination in different age groups. At the same time that it collects data, from the collaboration of the player, it enables a diagnosis with the perceptions about the misinformation involving vaccination. At the end of this study, it is concluded that the purposeful game can be explored by areas such as education and journalism, because it provides opportunities for the production of products aimed at combating disinformation through the use of attractive audiovisual resources capable of arousing the interest and engagement of different audiences.